2016
DOI: 10.2147/ce.s93717
|View full text |Cite
|
Sign up to set email alerts
|

Imiglucerase in the management of Gaucher disease type 1: an evidence-based review of its place in therapy

Abstract: IntroductionGaucher disease is the first lysosomal disease to benefit from enzyme replacement therapy, thus serving as model for numerous other lysosomal diseases. Alglucerase was the first glucocerebrosidase purified from placental extracts, and this was then replaced by imiglucerase – a Chinese hamster ovary cell-derived glucocerebrosidase.AimThe aim was to review the evidence underlying the use of imiglucerase in Gaucher disease type 1Evidence reviewData from clinical trials and Gaucher Registries were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 72 publications
2
11
0
2
Order By: Relevance
“…Though both groups benefitted from therapy, early start of treatment seems warranted, as irreversible complications were only visible in the "late" treatment group. This finding was consistent with current knowledge of Gaucher disease and consecutive treatment recommendations [1,10,23].…”
Section: A B C D E Fsupporting
confidence: 91%
See 1 more Smart Citation
“…Though both groups benefitted from therapy, early start of treatment seems warranted, as irreversible complications were only visible in the "late" treatment group. This finding was consistent with current knowledge of Gaucher disease and consecutive treatment recommendations [1,10,23].…”
Section: A B C D E Fsupporting
confidence: 91%
“…Several studies have demonstrated the effectiveness of ERT during the first years of treatment, based on MRI analyses [7,18]. Usually, after ERT initiation in Gaucher disease major response occurs within the first years [1,23], following a first order kinetic, while later on only small changes occur. Despite the relatively short follow-up after long-term ERT, our data also suggests at least disease stabilization with hints for possible slight improvements concerning bone involvement.…”
Section: A B C D E Fmentioning
confidence: 99%
“…Striking and rapid reversal of many of the overt aspects of type 1 Gaucher disease were seen in pivotal clinical trials of alglucerase and and later with the recombinant form of the enzyme, imiglucerase (Genzyme, Cambridge, MA, USA) and have been replicated again and again in small series of patients from single centers as well as a global, industry-sponsored multinational registry comprising almost 6,000 patients that collectively harbor ~54,000 patient-years of enzyme therapy experience [106]. Enzyme replacement therapy has proven highly effective in reversing hepatosplenomegaly, cytopenia, osteopenia, especially in children and young adults, and in reducing the risk of avascular osteonecrosis [107].…”
Section: Current Therapies For Gaucher Diseasementioning
confidence: 99%
“…имиглюцеразы сочетается с хорошей переносимостью и отсутствием выраженных побочных эффектов в лечении пациентов различного возраста с БГ 1-го и 3-го типов [7,9,10]. В июне 2009 г. фармацевтическая компания Джензайм Лтд.…”
Section: фармакотерапияunclassified
“…Для 1-й и 2-й групп добровольцев статистически значимых различий между препаратами по показателям T 1 / 2 и K el не выявлено (p >0,05). Полученные в исследовании результаты по указанным фармакокинетическим параметрам согласуются с данными литературы по препарату имиглюцераза [9,10]. В настоящем исследовании не выявлено статистически значимого (p >0,05) влияния последовательности введения ИП -отсутствует эффект периода введения препарата, а также не отмечено парного взаимодействия период × препарат (см.…”
Section: фармакотерапияunclassified